Selective Inhibition of Bromodomain-Containing Protein 4 Reduces Myofibroblast Transdifferentiation and Pulmonary Fibrosis - Bernau, Ksenija; Skibba, Melissa; Leet, Jonathan P.; Furey, Sierra; Gehl, Carson; Li, Yi; Zhou, Jia; Sandbo, Nathan; Brasier, Allan R. (Frontiers in Molecular Medicine, 2022)
Idiopathic pulmonary fibrosis is a lethal disease driven by myofibroblast expansion. Currently no therapies exist that target the epigenetic mechanisms controlling myofibroblast transdifferentiation, which is responsible for unregulated extracellular matrix (ECM) production. We have recently shown that bromodomain-containing protein 4 (BRD4), an epigenetic regulator that forms a scaffold for nuclear activators and transcription factors, is essential for TGFβ-induced myofibroblast transdifferentiation. However, its role in the development and progression of pulmonary fibrosis in vivo has not been established. Here, we evaluate the hypothesis that BRD4 bromodomain interactions mediate myofibroblast expansion and fibrosing disease in vivo. C57BL/6J mice challenged with intratracheal bleomycin were systemically treated with a selective allosteric inhibitor of the BRD4 bromodomain 1 (BD1), ZL0591 (10 mg/kg), during the established fibrotic phase (14 days post-bleomycin) in a rigorous therapeutic paradigm. Eleven days after initiation of ZL0591 treatment (25 days post-bleomycin), we detected a significant improvement in blood O2 saturation compared to bleomycin/vehicle control. Twenty-eight days post-bleomycin, we observed a reduction in the volumetric Hounsfield Unit (HU) density by micro computed tomography (µCT) in the ZL0591-treated group, as well as a reduction in collagen deposition (hydroxyproline content) and severity of injury (Ashcroft scoring). Myofibroblast transdifferentiation was measured by smooth muscle α-actin (αSMA) staining, indicating a loss of this cell population in the ZL0591-treated group, and corresponded to reduced transcript levels of myofibroblast-associated extracellular matrix genes, tenascin-C and collagen 1α1. We conclude that BRD4 BD1 interactions are critical for myofibroblast transdifferentiation and fibrotic progression in a mouse model of pulmonary fibrosis.